Directional Radiation Technique for Maximum Receiving Power in Microwave Power Transmission System - Hui, Qi; Jin, Ke; Zhu, Xirui (IEEE transactions on industrial electronics (1982), 2020)
Directional radiation (DR), a distinguishing feature of a microwave power transmission (MPT) system, suitably shapes and properly steers an intensified beam toward a specific target area. Coupling more radiated energy to the receiving aperture, DR technique benefits system efficiency and brings great flexibility, which entails further investigation. This article addresses DR realization from a system perspective. A novel architecture of MPT transmitter is proposed, which equips the system with multiple independently controlled RF power outputs and serves as a solid hardware basis for DR realization. Three DR algorithms are also introduced, providing convenient methods to obtain maximum receiving power for the receiver via software control. A 915 MHz/100 W MPT transmitter is fabricated in the lab, and an MPT verification platform is also constructed. Proposed architecture and algorithms are fully verified with experiments, which show a good performance in DR realization.